Mewujudkan Sustainable Development Goals (SDGs) di Desa Melalui Program Mahasiswa KKN - Setyoningsih, Budi (Yayasan Daarul Huda Kruengmane, 2024)
This research explores efforts to implement Sustainable Development Goals (SDGs) at the village level through the Community Service Program (KKN) which involves students. The research method uses a qualitative approach with in-depth interviews and participant observation as data collection techniques. This research was conducted in Wiroditan Village, Bojong District, Pekalongan Regency. The results of this research show that the implementation of SDGs in this village includes education and public health promotion, improving educational facilities, and business development and digital marketing workshops for women. Research findings show that through collaboration between students, village government and local communities, various programs that support the achievement of SDGs have been implemented in the village. This research provides valuable insights for parties involved in sustainable development at the local level.